Palmar dermatoglyphic traits in type 2 diabetes mellitus patients of Bengalee Hindu caste population of West Bengal, India: a cross-sectional study - Ghosh, Jyoti Ratan; Dastidar, Piya Ghosh; Dey, Biswarup; Das, Piyali; Bandyopadhyay, Arup Ratan (Journal of Biomedical Sciences, 2018)
Background Dermatoglyphics is frequently used in understanding the proximity with non-communicable diseases including diabetes mellitus. Diabetes mellitus is one of the most common non-communicable diseases all over the world. The present study is an attempt to understand the association of palmer dermatoglyphic traits [i.e. a-b ridge count (ABRC), c-d ridge count (CDRC), presence of multiple number of axial triradii (t, t' & t") in a single palm, td ridge count (TDRC), atd angle, btd angle and ctd angle] with type 2 diabetes mellitus (T2DM). Material and methods Subjects included 30 clinically diagnosed adult female T2DM patients and 60 healthy controls from the Bengalee Hindu Caste population of West Bengal, India. Bilateral palm prints were collected following standard ink and roller method. Results Present study revealed that T2DM patients have significantly (p<0.05) lower ABRC, CDRC and TDRC. On the other hand, significantly (p<0.05) higher presence of multiple number of axial triradii t, t' & t" was found in the palm of T2DM patients compared to the controls. T2DM patients also demonstrated significantly (p<0.05) higher values of atd and btd angle. However, T2DM patients demonstrated significantly (p<0.05) lower value of ctd angle than that of controls, only when both hand were considered. Conclusion The results the present study indicated that dermatoglyphic traits may be used for early identification of at risk individuals for surveillance with a view to prevent the disease onset. Journal of Biomedical Sciences, Vol. 3, No. 2, 2016